Low Sun Exposure as a Dominant Risk Factor of Hypertension Among Adolescents in SMPN 21 South Tangerang (Jurnal Ilmu Kesehatan Masyarakat, 2023)
Hypertension is a global health problem that can occur in adolescents. According to Riskesdas 2018, the national prevalence of hypertension is 34.1%. In Banten Province, it stands at 29.4%, and in South Tangerang City, it’s 27.5%. This study was aimed to determine the association between age, sex, vitamin D intake, fat intake, and sun exposure with the incidence of hypertension among adolescents at SMPN 21 South Tangerang and the dominant factor among these variables that is a risk factor of hypertension. This study used a cross-sectional design with a sample of 102 respondents taken using a stratified random sampling technique. Data were collected through blood pressure measurements, the Sun Exposure Questionnaire (SEQ), and the Semi Quantitative Food Frequency Questionnaire (SQ-FFQ). Association analysis was conducted using the chi-square test and Fisher's exact test, showing that there was an association between sun exposure (<0.05; OR = 7.902) with the incidence of hypertension, and there were no association between age (p = 0.556), sex (p = 0.386), vitamin D intake (p = 0.760), and fat intake (p = 1.000) with the incidence of hypertension among adolescents at SMPN 21 South Tangerang. The result of multivariate analysis using the regression logistic test showed that sun exposure was the most correlated factor of hypertension among adolescents at SMPN 21 South Tangerang (p = <0.05; OR = 7.949). Respondents should have more sun exposure to prevent hypertension.